Estimate bioaccumulation factors and antioxidative response in land snail rumina decollata exposed to pb and Cu in Diyala Province, Iraq - Farman, Khansaa S. (Edelweiss Applied Science and Technology, 2025)
This work aimed to determine the concentration of heavy metals, their bioaccumulation factors, and glutathione levels in the terrestrial snail Rumina decolata collected from three districts: Khanaqin, Mandali, and Muqdadiya in Diyala Governorate. In these districts, soil and snail samples were collected and analyzed using standard methods to determine metal concentrations. The results indicated that the soil and snails of Khanaqin had maximum levels of lead and copper, with mean values of 8.38 ± 2.85 and 3.51 ± 0.03 mg/kg in the soil samples and 1.09 ± 0.13 and 2.13 ± 0.91 mg/kg in snails, respectively. On the other hand, snail and soil samples in Muqdadiya had the lowest levels of such metals. Pb was not detected in snail samples. Bioaccumulation factor analysis showed a different level of accumulation, with a higher copper BCF than lead in Khanaqin, at 1.64 and 0.13, respectively, while the value of lead BCF was higher in Mandali, at 3.2. Additionally, the highest GSH level was observed in snails from Khanaqin, at 24±3.07 µmol/g, followed by Muqdadiya, at 19±1.4 µmol/g, and Mandali, at 17±0.9 µmol/g, which may reflect oxidative stress responses against metals. The above results highlight the potential role of Rumina decolata as a bioindicator for heavy metal pollution and demonstrate its role in heavy metal environmental contamination in Diyala Province. Variations in GSH levels and in the bioaccumulation factor reflect the differential adaptive response to ecological stresses.